Who's afraid of perfectionist moral enhancement? A reply to Sparrow. (22nd June 2020) - Huang, Pei‐hua
Abstract: Robert Sparrow recently argued that state‐driven moral bioenhancement is morally problematic because it inevitably invites moral perfectionism. While sharing Sparrow's worry about state‐driven moral bioenhancement, I argue that his anti‐perfectionism argument is too strong to offer useful normative guidance. That is, if we reject state‐driven moral bioenhancement because it cannot remain neutral between different conceptions of the good, we might have to conclude that all forms of moral enhancement programs ought not be made compulsory, including the least controversial and most popular state‐driven program: compulsory (moral) education. In this paper, I argue that, instead, the spirit of Sparrow's worry should be recast in the language of the capability approach—an approach that strives to enhance people's capabilities to develop their own conceptions of the good by restricting itself from endorsing thick conceptions of the good. The distinction made regarding thick and thin conceptions of the good helps to capture sentiments against state‐driven bioenhancement programs without falling prey to the issues I raise against Sparrow's anti‐perfectionist arguments.